2020
DOI: 10.1108/ijopm-11-2019-0724
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cultural value orientations on responses to supply-side disruption

Abstract: PurposePast research has shown that culture has significant effects on people's evaluation of and responses to risk. Despite this important role, the supply chain risk literature has been silent on this matter. The purpose of this paper is to examine the impact of cultural value orientations on managerial perception of and responses to a supply disruption risk.Design/methodology/approachThe authors conduct a scenario-based experiment to investigate the effect of cultural value orientations – i.e. individualism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 105 publications
(184 reference statements)
3
27
0
Order By: Relevance
“…Lastly, our paper contributes to the supply disruption management literature that offers empirical evidence of the consequences of supply disruptions Singhal, 2003, 2005;Zsidisin et al, 2016;Hendricks et al, 2020;Sarafan et al, 2020;Son et al, 2020). Prior studies have identified operational (Hendricks and Singhal, 2005) and economic impacts of disruptions (Hendricks and Singhal, 2003;Zsidisin et al, 2016).…”
Section: Theoretical Contributionsmentioning
confidence: 92%
See 2 more Smart Citations
“…Lastly, our paper contributes to the supply disruption management literature that offers empirical evidence of the consequences of supply disruptions Singhal, 2003, 2005;Zsidisin et al, 2016;Hendricks et al, 2020;Sarafan et al, 2020;Son et al, 2020). Prior studies have identified operational (Hendricks and Singhal, 2005) and economic impacts of disruptions (Hendricks and Singhal, 2003;Zsidisin et al, 2016).…”
Section: Theoretical Contributionsmentioning
confidence: 92%
“…A third theme focuses on identifying the economic and non-economic consequences of supply disruptions (cf. Singhal, 2003, 2005;Zsidisin et al, 2016;Polyviou et al, 2018;Chen et al, 2019;Hendricks et al, 2020;Sarafan et al, 2020;Son et al, 2020). Hendricks and Singhal (2003), for example, reported that firms announcing supply disruptions experience an average decline of 11% in their stock price.…”
Section: Ijopm 433mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, scenario-based experiments are an established technique for OM studies grounded in social psychology (see for example Ried et al. , 2021; Sarafan et al. , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Scenario-based experiments can reduce the influence of possible desirability bias (Rungtusanatham et al, 2011). In general, scenario-based experiments are an established technique for OM studies grounded in social psychology (see for example Ried et al, 2021;Sarafan et al, 2020).…”
Section: Methodsmentioning
confidence: 99%